Features of Catatonia in a 12-Year-Old Boy with Autism Spectrum Disorder. Issue 3 (April 2019) - Irwin, Margaret; Harstad, Elizabeth; Deister, Diana; Augustyn, Marilyn
Abstract : CASE: Thomas is a 12-year-old boy with autism spectrum disorder who presents to his primary care clinician with symptoms of worsening mood in the last 3 months. On review of his last school testing, his cognitive abilities are found to be within the average range, with a relative vulnerability with his processing speed. He can speak in sentences to communicate and answer questions, but he rarely picks up on conversational bids. He has had difficulties developing friendships and often prefers to play by himself. Thomas has a long history of some features of anxiety and depression for which it was recommended that he establish care with a therapist, but his family has had a hard time finding a provider for him. At this visit, the mother reports that for the past several months he has been more anxious, sad, and easily overwhelmed. He seems irritable at home and school and cries often. His family has been advocating for him to receive increased school supports, as school is a source of anxiety for him, but there are no recent changes in school services. There is a family history of both anxiety and depression. Given his worsening mood functioning, Thomas was started on selective serotonin reuptake inhibitor (SSRI) medication in addition to again recommending a therapist. Weekly phone call check-ins and an in-person clinic visit in 1 month are planned. About 1 month after starting the SSRI medication, he is still not showing any improvement in mood functioning, and his family reports he seems more "sluggish" than usual. There are no side effects reported with the medication, and the dose is increased to see whether it will help. However, about 2 weeks later, he is seen again in the clinic because there are increasing concerns. He continues to be "sluggish." During the clinic visit, he lies down on the examination table, sometimes holding his head off the edge of the table, which he has never done before. He responds very slowly to the questions and often says "I don't know, I don't know, " almost in an automatic way. His mother reports that he is now engaging in some repetitive hand movements which he had not done previously. He is no longer able to shower independently. He is still eating and drinking adequately. What would you do next?